2013
DOI: 10.1016/j.tsc.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to creativity: How adolescents engage in the creative process

Abstract: a b s t r a c tDespite growing recognition of creativity's importance for young people, the creativity of adolescents remains a neglected field of study. Hence, grounded theory research was conducted with 20 adolescents from two Australian schools regarding their self-reported experiences of creativity in diverse domains. Four approaches to the creative processadaptation, transfer, synthesis, and genesis -emerged from the research. These approaches used by students across a range of domains contribute to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 22 publications
3
30
0
2
Order By: Relevance
“…In general, the learner's perspective on creative and artistic development in early adolescence-the middle school years-is lacking in the literature on arts integration, arts education, and the learning sciences (Lassig, 2013;Moorefield-Lang, 2010;Rostan, 1998Rostan, , 2010. Lassig (2013) found four approaches to adolescents' creative process-adaptation, transfer, synthesis, and genesis-but only included students with perceived high levels of creative characteristics and focused solely on the inward process. In this current study, we organize the early adolescent perspective from diverse students within the socio-cultural setting of a classroom, looking for both the inward and outward process of their creative engagement.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the learner's perspective on creative and artistic development in early adolescence-the middle school years-is lacking in the literature on arts integration, arts education, and the learning sciences (Lassig, 2013;Moorefield-Lang, 2010;Rostan, 1998Rostan, , 2010. Lassig (2013) found four approaches to adolescents' creative process-adaptation, transfer, synthesis, and genesis-but only included students with perceived high levels of creative characteristics and focused solely on the inward process. In this current study, we organize the early adolescent perspective from diverse students within the socio-cultural setting of a classroom, looking for both the inward and outward process of their creative engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a crucial period to develop creative potential, in both cognitive aspects (Kleibeuker, De Dreu, & Crone, ; Lassig, ; Stevenson, Kleibeuker, de Dreu, & Crone, ) and noncognitive aspects (Barbot, ; Barbot & Heuser, ; Rothenberg, ; Schaefer, ). During this crucial period, adolescents experience the paradox between building a sense of uniqueness and seeking acceptance from important others, especially from peers.…”
mentioning
confidence: 99%
“…The results of study showed that cloud‐based m‐learning had a positive effect on the overall creative process in engineering design, as well as on performance at various stages. With regard to creative processes, a large amount of information is needed as the basis for creative cognition, creative thinking and problem solving (Cropley, ; Lassig, ). Multimedia presentations in cloud‐based m‐learning enabled multisensory stimulation and thinking (Huang et al , ), while proactive and real‐time interaction furthered brainstorming activities (Lin et al , ; Zurita et al , ).…”
Section: Discussionmentioning
confidence: 99%